2022
DOI: 10.3389/fphar.2022.963245
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic efficacy of resveratrol for acute lung injury—A meta−analysis of preclinical trials

Abstract: Background: Resveratrol (RES) has a protective effect on acute lung injury (ALI) or acute respiratory distress syndrome (ARDS). Our purpose was to conduct a meta−analysis to investigate the efficacy of RES for ALI/ARDS in animal models.Methods: PubMed, EMBASE and Web of Science were searched to screen relevant preclinical trials. The standardized mean difference (SMD) was used to compare the lung injury score, lung wet−dry weight ratio (W/D ratio), tumor necrosis factor−α (TNF−α), interleukin−1β (IL−1β), IL−6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Resveratrol (RSV), a polyphenolic nutraceutical mainly found in grapes ( Vitis vinifera L.) ( Figure 3 ), demonstrates health-promoting properties, including antioxidative [ 61 ], immunomodulatory [ 62 ], and anti-aging effects [ 63 ]. Since its association with the “French paradox” in 1992, resveratrol has received increasing research interest owing to its diverse pharmacological activities and multi-organ protective effects (e.g., acute lung injury [ 64 ], cerebral ischemia/reperfusion injury [ 65 ], myocardial cell apoptosis [ 66 ], and hepatic injury [ 67 ]). Resveratrol is classified as a food supplement with an excellent safety record and no serious adverse events even when administered in large doses (up to 600 mg per day) [ 68 ].…”
Section: Resveratrol and Its Natural Derivatives—grape-derived Ace2 I...mentioning
confidence: 99%
“…Resveratrol (RSV), a polyphenolic nutraceutical mainly found in grapes ( Vitis vinifera L.) ( Figure 3 ), demonstrates health-promoting properties, including antioxidative [ 61 ], immunomodulatory [ 62 ], and anti-aging effects [ 63 ]. Since its association with the “French paradox” in 1992, resveratrol has received increasing research interest owing to its diverse pharmacological activities and multi-organ protective effects (e.g., acute lung injury [ 64 ], cerebral ischemia/reperfusion injury [ 65 ], myocardial cell apoptosis [ 66 ], and hepatic injury [ 67 ]). Resveratrol is classified as a food supplement with an excellent safety record and no serious adverse events even when administered in large doses (up to 600 mg per day) [ 68 ].…”
Section: Resveratrol and Its Natural Derivatives—grape-derived Ace2 I...mentioning
confidence: 99%
“…A few studies have found that RES could prevent and treat various cancers, such as breast, gastric, colorectal, prostate, and lung cancers (Wu et al, 2022). Therefore, considering its low toxicity to normal tissues, RES has been used in preclinical and clinical research (Mansour et al, 2021; A. P. Singh et al, 2019; Tang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considering its low toxicity to normal tissues, RES has been used in preclinical and clinical research (Mansour et al, 2021;A. P. Singh et al, 2019;Tang et al, 2022).…”
mentioning
confidence: 99%
“…Acute lung injury (ALI) is an acute inflammatory condition often triggered by severe infection or trauma. It is characterized by difficulty in breathing, respiratory distress, and damage to the alveolar epithelial barrier (1,2). The primary pathological features include acute widespread alveolar damage, pulmonary interstitial fluid accumulation, heightened pulmonary capillary permeability, and excessive inflammation (3,4).…”
Section: Introductionmentioning
confidence: 99%